2021
DOI: 10.4081/ejh.2021.3242
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry as a paramount tool in research of normal urothelium, bladder cancer and bladder pain syndrome

Abstract: The urothelium, an epithelium of the urinary bladder, primarily functions as blood-urine permeability barrier. The urothelium has a very slow turn-over under normal conditions but is capable of extremely fast response to injury. During regeneration urothelium either restores normal function or undergoes altered differentiation pathways, the latter being the cause of several bladder diseases. In this review, we describe the structure of the apical plasma membrane that enables barrier function, the role of uroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 107 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…UC, the major type of BLCA, is a cancer of the epithelial cells destined to be closely related to keratin. Different molecular subtypes of UC commonly have different keratin levels [ 51 ], and keratin expression profiles have been recognized as diagnostic and prognostic markers for BLCA [ 52 ]. According to recent studies, Keratin 17 (K17) targets tumour suppressors and mediates signals to promote tumour growth [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…UC, the major type of BLCA, is a cancer of the epithelial cells destined to be closely related to keratin. Different molecular subtypes of UC commonly have different keratin levels [ 51 ], and keratin expression profiles have been recognized as diagnostic and prognostic markers for BLCA [ 52 ]. According to recent studies, Keratin 17 (K17) targets tumour suppressors and mediates signals to promote tumour growth [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that four of five uroplakins, UPK1A , 1B , 2 , and 3A , were highly expressed in the bladder body urothelium. Immunohistochemical assays have shown that uroplakin expression was reduced in intermediate cells and largely absent in basal cells [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…They play roles in normal and pathological processes, including allergic responses, infectious and autoimmune diseases, inflammation, and angiogenesis [ 55 , 56 ]. Most of the main pathologic conditions of the bladder, including cancer, urinary tract infections, and BPS/IC, may significantly affect the expression of urothelial receptors and channels, resulting in micturition dysfunctions [ 42 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancerbladder is a prevalent disease associated with substantial morbidity, mortality, and costs. Environmental or occupational exposure to carcinogens, especially tobacco, is a significant risk factor for bladder cancer (Sanli et al, 2017;Zupančič, 2021). In much of the world, smoking and chemical exposure are major risk factors for bladder cancer (Grayson, 2017).…”
Section: Introductionmentioning
confidence: 99%